2
$\begingroup$

I'm trying to prove that, given $(u_n)_n \in \mathbb{C}^\mathbb{N}$ verifying $ u_{n+1}-u_n =_{n} o(\frac{1}{n})$, the following holds:

$$ \lim_{n\to\infty} \frac{u_1+...+u_n}{n} = a \in \mathbb{C} \implies \lim_{n\to\infty} u_n = a$$

It is the reciprocal to the Cesaro 'average theorem'.

An indication is given, to rewrite the average using $u_n$ and $a_k = u_k - u_{k-1}$ (with $a_1=u_1$) which I have figured out to be:

$$u_1+...+u_n = u_n + \sum\limits_{k=1}^n \sum\limits_{i=1}^k a_i$$

What I've tried doing is rewriting this double sum, which I've found to be a $o\big(ln(\small(n+1\small)!)\big)$. Other than that, most of my attempts have proven futile to solving this.

$\endgroup$
3
$\begingroup$

Define $a_1=u_1$ and $a_n=u_{n}-u_{n-1}$ for $n\geq 2$.

Note that $$\begin{align} u_n-\frac{S_n}n &= u_n-\frac 1n \sum_{k=1}^nu_k \\ &=u_n-\frac 1n \sum_{k=1}^n \sum_{j=1}^k a_k \\ &=u_n-\frac 1n \sum_{j=1}^n\sum_{k=j}^n a_j\\ &=u_n-\frac 1n \sum_{j=1}^na_j\sum_{k=j}^n 1\\ &=\sum_{j=1}^n a_j-\frac 1n \sum_{j=1}^n (n-j+1)a_j\\ &=\frac{1}n\sum_{j=1}^n (j-1)a_j \end{align}$$

Since $na_n\to0$, $(n-1)a_n\to0$ and the usual Cesaro theorem yields $\lim_{n\to \infty} \frac{1}n\sum_{j=1}^n (j-1)a_j=0$.

This implies $\displaystyle \lim_n (u_n-\frac{S_n}n)=0$, hence $\lim_n u_n=a$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.